(untitled) (Research, Society and Development, 2021)
Objective: To determine whether the performance of acute and chronic physical exercises produces significant changes in the metabolic and cardiovascular components, especially in the lipid profile of individuals diagnosed with metabolic syndrome (MS). Methods: Search conducted in journals indexed in the electronic databases MEDLINE / PUBMED, LILACS and SCIELO about the effects of isometric exercises in individuals with MS. The inclusion criteria for the studies analyzed were: studies published between 2010 and 2020; studies published in English and Portuguese (the last being in indexed journals); sample of individuals over 40 years of age; presence of alteration in the participants’ lipid profile; assessment of the lipid profile by table and / or portable devices and original articles. Results: Among the studies found in this review, 12 articles met the proposed criteria. Aerobic exercises were the most recurrent present in 5 studies, followed by combined exercise with aerobic and strength training totaling 4 articles, in addition to showing a decrease in parameters related to MS, especially in the lipidogram. Furthermore, evidence suggests that the association between a calorie-restricted diet and combined exercises are essential tools for reducing the parameters of MS. Conclusion: Evidence suggests that physical exercise has several positive systemic effects on individuals with metabolic syndrome; mainly elderly people through muscle strengthening, body coordination, reduction of falls, optimization of cardiorespiratory performance, among others.